The Impact of Perceived Organizational Justice on Negative Work Behaviors - A Field Study at The Public Institution for Neighborhood Health in Jijel - - .DJEBLI, hassiba (Journal of Excellence for Economics and Management Research, 2021)
The study aimed to identify the level of the organizational justice (distributive justice, procedural justice, practical justice) among the workers at the public institution for neighborhood health 40 Hectare in Jijel, and to measure their attitudes towards practicing negative work behaviors. It also aimed to identify the impact of organizational justice on negative work behaviors. To achieve the goal, a questionnaire was designed for the purpose of collecting the data. through a sample of 34 employees who were randomly chosen. The data collected through questionnaire was subjected to a number of statistical methods by using (SPSS). The descriptive analytical approach was adopted in the study. The most important results found by this study is the presence of an average level of feeling of organizational justice, as well as a low level of negative work behaviors. In addition, the study did not reveal any significant effect of the dimensions of organizational justice on negative work behaviors